Describing the Ability of Science Processes in Basic Physics Practicum II Material of Ice Melting Heat Using E-Modules - Winda, Febrina Rosa; Shofiardin, M (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The purpose of this study was to determine the level of students' science process skills and to determine the effect of using e-modules in the Basic Physics II practicum with the material melting heat of ice. Methodology: This research is a type of quantitative research with descriptive methods. The subjects in this study were 40 second semester students of Physics Education at Jambi University. The data collection instrument used was an observation sheet of science process skills that had been validated previously to assess students' science process skills in carrying out practicums. Data collection was carried out with the help of an observer who observed each student and the data was analyzed using statistical analysis. Main Findings: Based on the results of data analysis, it shows that the use of e-modules is effective in carrying out practicums and the average student science skill level is in the SB category (very good). Novelty/Originality of this study: The novelty of the research can be seen from the results of the research that has been done. It is evident that the E-module, apart from being easy to access and easy to carry around, also contains detailed information regarding practicum material. This is because the e-module is packaged in a web form that students can access anywhere and anytime, whereas using a conventional guide will result in a lack of efficiency because the more material is included, the heavier it will be and the more paper used to print the guide.